Remote Effects of IOD and ENSO on Motivating the Atmospheric Pattern Favorable for Snowfall Over the Tibetan Plateau in Early Winter - Shen, Hongyan; Gong, Zhiqiang; Liu, Boqi; Guo, Yipeng; Feng, Xiaoli; Wen, Tingting; Wang, Xiaojuan; Feng, Guolin (Frontiers in Climate, 2021)
The interannual variation of snowfall over the Tibetan Plateau (TP) in early winter (November–December) and its related atmospheric attribution are clarified. Meanwhile, the influence of tropical sea surface temperatures (SSTs) on TP snowfall is investigated by diagnostic analyses and Community Atmosphere Model (CAM5) simulations. The leading mode of TP snowfall in early winter features a spatially uniform pattern with remarkable interannual variability. It is found that the Indian Ocean Dipole (IOD) and El Niño Southern Oscillation (ENSO) are main external forcing factors for TP snowfall. Positive IOD with positive ENSO and positive IOD with neutral ENSO cases both have remote impact on motivating Southern Eurasia (SEA) pattern, which can induce an anomalous cyclone around the TP. The corresponding anomalous ascending motion and cold air in the mid-upper troposphere provide the dynamical and thermal conditions for heavy snowfall. The low-level southwesterly winds are enhanced over the Arabian Sea and Bay of Bengal, bringing abundant water vapor into the TP for excessive snowfall. Furthermore, CAM5 simulation experiments forced by IOD- and ENSO-related SST anomalies are performed to verify their combined and independent effects on TP snowfall in early winter. It is confirmed that either positive IOD or El Niño has certain impacts on motivating circulation anomalies favorable for snowfall over the TP. However, IOD plays a leading role in producing the excessive snowfall-related atmospheric conditions, and there is an asymmetric influence of ENSO and IOD on the TP snowfall.